MODIFIKASI FONOLOGIS BAHASA PROKEM DI MEDIA SOSIAL (TIKTOK, INSTAGRAM, X DAN YOUTUBE) - Septiana, Fina Dwi; Amilia, Fitri; Anggraeni, Astri Widyaruli (Universitas Batanghari, 2024)
This research aims to describe the form of phonological modification of Prokem language on social media (Tiktok, Instagram, X, and Youtube) which consists of forms of vowel phoneme modification and consonant modification. The research method used is descriptive qualitative with data collection techniques using observation and note-taking documentation. The data in this research is in the form of spoken words in the form of modifications of vowel and consonant phonemes in prokem language on social media (Tiktok, Instagram, X, and Youtube). The data analysis technique used in this research uses the agih method with advanced techniques in the form of inserting and changing the form of paraphrasing. The results of this research show that the prokem language which has undergone vocal modification in the prokem language is divided into two categories, namely 1) pairs of vowel sound changes, 2) sound substitutions which are influenced by regional language dialect and environmental factors. On the other hand, consonant modification is the most common form of modification found in prokem language on social media which is divided into four forms, 1) pairs of consonant sound changes, 2) distribution of phoneme insertions, 3) flow of changes in foreign language absorption at the end of words, 4) escalation double consonant in the middle of a word. The form of consonant modification that often appears is the phoneme element [y] which is located in the first syllable, in the middle and at the end of words in prokem languages. Apart from that, the contribution to the development of the most popular variety of prokem language is in the form of teXt or vocabulary compared to the audio type on Instagram social media.